Pentingnya Manajemen Risiko dalam Pengambilan Keputusan di SatuanPendidikan - Marsya Dwi Anjelina; Irsyad, Irsyad; Merika Setiawati (CV. ITTC INDONESIA, 2025)
This study explores the importance of risk management in decision-making within educational institutions. The research aims to understand how risk management contributes to effective, accountable, and data-based decision-making in schools. A qualitative literature review was used to collect and analyze information from books, journals, and official documents related to risk management and school administration. The findings indicate that schools face various internal and external risks, including administrative errors, limited budgets, human resource challenges, policy changes, and environmental factors. Implementing risk management allows schools to anticipate potential problems, plan appropriate mitigation strategies, strengthen governance, and cultivate a risk-aware culture among staff and stakeholders. These practices improve the quality of education services and enhance the organization’s readiness to respond to challenges. In conclusion, risk management functions not only as a preventive tool but also as a strategic approach to optimize school performance and ensure sustainable educational outcomes.